Learning Sensory Nerve Coaptation in Free Flap Breast Reconstruction - Smeele, Hansje P.; Beugels, Jop; Kuijk, Sander M. J. van; Hulst, René R. W. J. van der; Tuinder, Stefania M. H. (Journal of Reconstructive Microsurgery, 2023)
Background The aims of this study were to assess whether sensory nerve coaptation in free flap breast reconstruction is subject to learning, and to elucidate challenges of this technique.Methods In this single-center retrospective cohort study, we reviewed consecutive free flap breast reconstructions performed between March 2015 and August 2018. Data were extracted from medical records, and missing values were imputed. We assessed learning by exploring associations between case number and probability of successful nerve coaptation using a multivariable mixed-effects model. Sensitivity analysis was performed in a subgroup of cases with evidence of attempted coaptation. Recorded reasons for failed coaptation attempts were grouped into thematic categories. Multivariable mixed-effects models were used to examine associations between case number and postoperative mechanical detection threshold.Results Nerve coaptation was completed in 250 of 564 (44%) included breast reconstructions. Success rates varied considerably between surgeons (range 21–78%). In the total sample, the adjusted odds of successful nerve coaptation increased 1.03-fold for every unit increase in case number (95% confidence interval 1.01–1.05, p < 0.05), but sensitivity analysis refuted this apparent learning effect (adjusted odds ratio 1.00, 95% confidence interval 1.00–1.01, p = 0.34). The most frequently recorded reasons for failed nerve coaptation attempts were inability to locate a donor or recipient nerve. Postoperative mechanical detection thresholds showed a negligible, positive association with case number (estimate 0.00, 95% confidence interval 0.00–0.01, p < 0.05).Conclusion This study does not provide evidence in support of a learning process for nerve coaptation in free flap breast reconstruction. Nevertheless, the identified technical challenges suggest that surgeons may benefit from training visual search skills, familiarizing with relevant anatomy, and practicing techniques for achieving tensionless coaptation. This study complements prior studies exploring therapeutic benefit of nerve coaptation by addressing technical feasibility.
Keywords: reconstructive surgery; free flap; breast reconstruction; sensory nerve coaptation; learning